Estudo do comportamento mecânico de vergas armadas com treliças planas em alvenaria estrutural - Rezende, Fabiana Martins de (2012)
The main goal of these studies were evaluate the mechanical behavior of structural masonry lintels built with hollow clay blocks. The compressive strength and failure mode of lintels under bending were determine using three different types of lintels: grouted and reinforced lintels made with U section blocks, structural blocks with horizontal prefabricated bedding joint reinforcements and horizontal and vertical joint reinforcements with MURFOR® steel reinforcement and stirrups. The test results indicated that the failures occur by shear strength. The use of lintels with grout demonstrated high levels of loading resistance, when compared with the others models. The use of horizontal and vertical reinforcement (MURFOR®), support higher level of loading, when it was compared with only horizontal joint reinforce.